PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN UKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Pertambangan yang terdaftar di Bursa Efek Indonesia pada Tahun 2022-2024) - Salwa Salsabila Nurman; Imam Ghozali (Diponegoro Journal of Accounting, 2026)
This study aims to test the influence of good corporate governance such as audit committee size, audit committee expertise, as well as auditor industry specialization and firm size on audit report lag, with audit quality as a moderating variable. The dependent variable in this study is audit report lag, while the independent variables in this study are audit committee size, audit committee expertise, and auditor industry specialization.The population in this study is mining companies listed on the Indonesia Stock Exchange in 2022-2024. A total of 360 samples were taken using the purposive sampling method with predetermined criteria. The data analysis method used is Moderated Regression Analysis (MRA) as a method to analyze independent and dependent variable, as well as moderating variable.The results of the study show that audit committee expertise and company size have a significant positive effect on audit report lag, while audit committee size and auditor industry specialization does not have a significant effect on audit report lag. Audit quality was found to moderate the effect of auditor industry specialization on audit report lag negatively or weakens the relationship between the two variables, while audit quality does not moderate the relationship between audit committee size, audit committee expertise, and company size towards audit report lag.